Inner electrode copper paste for low-temperature co-fired ceramic and preparation method of inner electrode copper paste
By pickling and sol-gel surface coating on the copper powder, and combining with the melt-water quenching method to prepare inorganic binders, the problems of degradation of conductivity and poor matching caused by the easy oxidation of copper powder are solved, and higher conductive properties and co-fired matching are achieved.
Patent Information
- Application Number
- CN202411890403.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The existing inner electrode copper slurry used for low-temperature cofiring ceramics has reduced conductivity due to the oxidation of copper powder and poor cofiring matching with the substrate.
The copper powder was pickled and sol-gel method to carry out surface coating of calcium/silver co-doped silica, combined with the melt-water quenching method, and finally, the inner electrode copper slurry was prepared by physically blending with the organic carrier.
It effectively reduces the oxidation of copper powder and improves co-fired matching and conductive properties with the substrate.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of internal electrode copper paste, and in particular relates to an internal electrode copper paste for low temperature co-fired ceramics and a preparation method thereof. Background Art
[0002] Low-temperature co-fired ceramics is a technology that co-fires multiple layers of ceramic green sheets at a relatively low temperature to form a multi-layer ceramic substrate. It is widely used in the fields of communications and electronics due to its many advantages such as high integration and strong compatibility. Among them, the internal electrode copper paste currently used for low-temperature co-fired ceramics is mostly prepared with copper powder, inorganic binder and organic carrier as raw materials. Although copper powder has better high-frequency characteristics and conductivity than gold, and smaller migration defects than silver, the copper powder itself has a small particle size and large specific surface area, making it extremely easy to oxidize, which leads to poor co-firing matching between the final internal electrode copper paste and the substrate and reduced conductivity. Summary of the invention
[0003] In view of the problems existing in the prior art, the purpose of the present invention is to provide an internal electrode copper paste for low-temperature co-fired ceramics and a preparation method thereof. The present invention creatively performs pickling on the copper powder first, and then performs surface coating of calcium / silver co-doped silica on the pickled copper powder based on a sol-gel method, thereby obtaining a pretreated copper powder. Subsequently, silicon dioxide, boron trioxide, barium oxide, aluminum oxide, titanium oxide and lanthanum oxide are used as raw materials, and an inorganic binder is prepared based on a melt-water quenching method, so that the two are simply physically blended with a conventional organic carrier to obtain an internal electrode copper paste, which is very suitable for application in low-temperature co-fired ceramics, effectively reducing the oxidation of the copper powder, improving the co-firing matching with the substrate, and enhancing the conductive performance.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] Disclosed is an internal electrode copper paste for low temperature co-fired ceramics. The internal electrode copper paste is prepared from pretreated copper powder, an inorganic binder and an organic carrier; the mass ratio of the pretreated copper powder, the inorganic binder and the organic carrier is 70-80:5-7:20.
[0006] As a preferred technical solution of the present invention, the pretreated copper powder is prepared by the following steps:
[0007] (1) adding 10-15 parts by weight of copper powder to 100 parts by weight of dilute hydrochloric acid solution, stirring and mixing at room temperature for 15-20 minutes, filtering and taking the filter residue, adding 80-100 parts by weight of acetone, stirring and mixing at 50-60° C. for 15-30 minutes, filtering and removing the filtrate, and finally vacuum drying at 60-70° C. until constant weight, to obtain component A;
[0008] (2) adding 0.1-0.3 parts by weight of deionized water, 0.8-1 parts by weight of tetraethyl orthosilicate and 1 part by weight of aqueous ammonia to 70-80 parts by weight of anhydrous ethanol, stirring and mixing at 30-40° C. for 45-60 minutes, keeping the temperature, then adding 0.05 parts by weight of calcium nitrate and 0.05-0.08 parts by weight of silver nitrate, stirring and mixing for 20-30 minutes, to obtain component B;
[0009] (3) Add 15-20 parts by weight of anhydrous ethanol and 3 parts by weight of component A to component B, then stir and mix at 60-65° C. for 6-8 hours, dry, and calcine to complete the preparation.
[0010] Furthermore, the mass fraction of the dilute hydrochloric acid solution in step (1) is 5-7%.
[0011] Furthermore, the mass fraction of the ammonia water in step (2) is 25%.
[0012] Furthermore, the drying in step (3) refers to vacuum drying at 80-90° C. for 2 h.
[0013] Furthermore, the calcination in step (3) refers to heating to 380° C. at a heating rate of 8-10° C. / min under a nitrogen atmosphere and then calcining for 1-2 hours.
[0014] As a preferred technical solution of the present invention, the inorganic binder is prepared by the following steps:
[0015] Silicon dioxide, boron trioxide, barium oxide, aluminum oxide, titanium oxide and lanthanum oxide are mixed in a mass ratio of 25-30:15-20:10:15-20:3-4:2, and then heated to 1500-1600°C at a heating rate of 10-15°C / min, kept at a constant temperature for 20-30 minutes, quenched in water, and then vacuum dried at 30-40°C until constant weight, ground, and the preparation is completed.
[0016] Furthermore, the grinding refers to grinding to a particle size of 1.5-1.8 μm.
[0017] As a preferred technical solution of the present invention, the organic carrier is prepared by the following steps:
[0018] Add 2 parts by weight of thickener to 25-30 parts by weight of solvent, then stir at 90-95°C until completely dissolved, cool naturally to room temperature, then add 1 part by weight of surfactant and 1.5-2 parts by weight of dispersant, continue stirring for 8-10 hours, and finally let stand naturally for 20-24 hours to complete the preparation.
[0019] Furthermore, the solvent is at least one of terpineol and butyl carbitol.
[0020] Furthermore, the thickener is ethyl cellulose.
[0021] Furthermore, the surfactant is polyethylene glycol 400.
[0022] Furthermore, the dispersant is dibutyl phthalate and castor oil; the mass ratio of the dibutyl phthalate to the castor oil is 2:1-1.5.
[0023] A method for preparing an inner electrode copper paste for low temperature co-fired ceramics, the preparation method comprising the following steps:
[0024] The pretreated copper powder, the inorganic binder and the organic carrier are stirred and mixed at a stirring speed of 300-500 rpm at room temperature for 5-10 minutes to complete the preparation.
[0025] Beneficial effects of the present invention:
[0026] (1) The present invention creatively performs pickling on copper powder first, and then performs surface coating of calcium / silver co-doped silica on the pickled copper powder based on a sol-gel method, thereby obtaining a pretreated copper powder. Subsequently, silicon dioxide, boron trioxide, barium oxide, aluminum oxide, titanium oxide and lanthanum oxide are used as raw materials, and an inorganic binder is prepared based on a melt-water quenching method, so that the two are simply physically blended with a conventional organic carrier to obtain an internal electrode copper slurry, which is very suitable for application in low-temperature co-fired ceramics, effectively reducing the oxidation of copper powder, improving the co-firing matching with the substrate, and enhancing the conductive performance.
[0027] (2) In order to solve the problem of easy oxidation of copper powder, the present invention creatively coats the surface of the pickled copper powder with calcium / silver co-doped silica based on the sol-gel method. On the one hand, silica can well act as a protective layer, thereby reducing the oxidation of copper powder, improving the co-firing matching of the subsequently prepared internal electrode copper paste and the substrate, and enhancing the conductive performance. On the other hand, after calcium / silver co-doping, the generated silica can have fewer micropore structures, further reducing the contact probability of copper powder and oxygen, and better playing the role of the protective layer. In addition, based on the main function of the inorganic binder to provide adhesion, the internal electrode copper paste and the substrate are firmly bonded. The present invention also creatively designs the formula of the inorganic binder by synergistically compounding six different metal oxides of silicon dioxide, boron trioxide, barium oxide, aluminum oxide, titanium oxide and lanthanum oxide, so as to further obtain a more excellent co-firing effect and promote conductive performance. DETAILED DESCRIPTION
[0028] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0029] The copper powder in all the embodiments and comparative examples of the present invention was purchased from Zhejiang Manli Nanotechnology Co., Ltd., model ML-Cu-W02; the ethyl cellulose was purchased from Chengdu Cologne Chemicals Co., Ltd., grade AR, powdered.
[0030] Example 1
[0031] Disclosed is an internal electrode copper paste for low temperature co-fired ceramics. The internal electrode copper paste is prepared from pretreated copper powder, an inorganic binder and an organic carrier; the mass ratio of the pretreated copper powder, the inorganic binder and the organic carrier is 70:5:20.
[0032] The pretreated copper powder is prepared by the following steps:
[0033] (1) adding 10 parts by weight of copper powder to 100 parts by weight of dilute hydrochloric acid solution, stirring and mixing at room temperature for 15 minutes, filtering and taking the filter residue, adding 80 parts by weight of acetone, stirring and mixing at 50° C. for 15 minutes, filtering and removing the filtrate, and finally vacuum drying at 60° C. until constant weight, to obtain component A;
[0034] (2) adding 0.1 parts by weight of deionized water, 0.8 parts by weight of tetraethyl orthosilicate and 1 part by weight of aqueous ammonia to 70 parts by weight of anhydrous ethanol, stirring and mixing at 30° C. for 45 minutes, keeping the temperature, and then adding 0.05 parts by weight of calcium nitrate and 0.05 parts by weight of silver nitrate, stirring and mixing for 20 minutes to obtain component B;
[0035] (3) Add 15 parts by weight of anhydrous ethanol and 3 parts by weight of component A to component B, then stir and mix at 60° C. for 6 hours, dry, and calcine to complete the preparation.
[0036] The mass fraction of the dilute hydrochloric acid solution in step (1) is 5%.
[0037] The mass fraction of the ammonia water in step (2) is 25%.
[0038] The drying in step (3) refers to vacuum drying at 80° C. for 2 h.
[0039] The calcination in step (3) refers to heating to 380°C at a heating rate of 8°C / min under a nitrogen atmosphere and then calcining for 1 hour.
[0040] The inorganic binder is prepared by the following steps:
[0041] Silicon dioxide, boron trioxide, barium oxide, aluminum oxide, titanium oxide and lanthanum oxide are mixed in a mass ratio of 25:15:10:15:3:2, and then heated to 1500°C at a heating rate of 10°C / min and kept at a constant temperature for 20 minutes, quenched in water, and then vacuum dried at 30°C until constant weight, and ground to complete the preparation.
[0042] The grinding refers to grinding to a particle size of 1.5 μm.
[0043] The organic carrier is prepared by the following steps:
[0044] Add 2 parts by weight of thickener to 25 parts by weight of solvent, then stir at 90°C until completely dissolved, cool naturally to room temperature, then add 1 part by weight of surfactant and 1.5 parts by weight of dispersant, continue stirring for 8 hours, and finally let stand naturally for 20 hours to complete the preparation.
[0045] The solvent is terpineol.
[0046] The thickener is ethyl cellulose.
[0047] The surfactant is polyethylene glycol 400.
[0048] The dispersants are dibutyl phthalate and castor oil; the mass ratio of the dibutyl phthalate to the castor oil is 2:1.
[0049] A method for preparing an inner electrode copper paste for low temperature co-fired ceramics, the preparation method comprising the following steps:
[0050] The pretreated copper powder, the inorganic binder and the organic carrier are stirred and mixed at a stirring speed of 300 rpm at room temperature for 5 minutes to complete the preparation.
[0051] Example 2
[0052] Disclosed is an inner electrode copper paste for low temperature co-fired ceramics. The inner electrode copper paste is prepared from pretreated copper powder, an inorganic binder and an organic carrier; the mass ratio of the pretreated copper powder, the inorganic binder and the organic carrier is 80:7:20.
[0053] The pretreated copper powder is prepared by the following steps:
[0054] (1) adding 15 parts by weight of copper powder to 100 parts by weight of a dilute hydrochloric acid solution, stirring and mixing at room temperature for 20 minutes, filtering and taking the filter residue, adding 100 parts by weight of acetone, stirring and mixing at 60° C. for 30 minutes, filtering and removing the filtrate, and finally vacuum drying at 70° C. until constant weight, to obtain component A;
[0055] (2) adding 0.3 parts by weight of deionized water, 1 part by weight of ethyl orthosilicate and 1 part by weight of aqueous ammonia to 80 parts by weight of anhydrous ethanol, stirring and mixing at 40° C. for 60 minutes, keeping the temperature, then adding 0.05 parts by weight of calcium nitrate and 0.08 parts by weight of silver nitrate, stirring and mixing for 30 minutes, to obtain component B;
[0056] (3) Add 20 parts by weight of anhydrous ethanol and 3 parts by weight of component A to component B, then stir and mix at 65° C. for 8 h, dry, and calcine to complete the preparation.
[0057] The mass fraction of the dilute hydrochloric acid solution in step (1) is 7%.
[0058] The mass fraction of the ammonia water in step (2) is 25%.
[0059] The drying in step (3) refers to vacuum drying at 90° C. for 2 h.
[0060] The calcination in step (3) refers to heating to 380°C at a heating rate of 10°C / min under a nitrogen atmosphere and then calcining for 2h.
[0061] The inorganic binder is prepared by the following steps:
[0062] Silicon dioxide, boron trioxide, barium oxide, aluminum oxide, titanium oxide and lanthanum oxide are mixed in a mass ratio of 30:20:10:20:4:2, and then heated to 1600°C at a heating rate of 15°C / min and kept at a constant temperature for 30 minutes, quenched in water, and then vacuum dried at 40°C until constant weight, and ground to complete the preparation.
[0063] The grinding refers to grinding to a particle size of 1.8 μm.
[0064] The organic carrier is prepared by the following steps:
[0065] Add 2 parts by weight of thickener to 30 parts by weight of solvent, then stir at 95°C until completely dissolved, cool naturally to room temperature, then add 1 part by weight of surfactant and 2 parts by weight of dispersant, continue stirring for 10 hours, and finally let stand naturally for 24 hours to complete the preparation.
[0066] The solvent is terpineol.
[0067] The thickener is ethyl cellulose.
[0068] The surfactant is polyethylene glycol 400.
[0069] The dispersants are dibutyl phthalate and castor oil; the mass ratio of the dibutyl phthalate to the castor oil is 2:1.5.
[0070] A method for preparing an inner electrode copper paste for low temperature co-fired ceramics, the preparation method comprising the following steps:
[0071] The pretreated copper powder, the inorganic binder and the organic carrier are stirred and mixed at a stirring speed of 500 rpm at room temperature for 10 minutes to complete the preparation.
[0072] Example 3
[0073] Disclosed is an inner electrode copper paste for low temperature co-fired ceramics. The inner electrode copper paste is prepared from pretreated copper powder, an inorganic binder and an organic carrier; the mass ratio of the pretreated copper powder, the inorganic binder and the organic carrier is 75:6:20.
[0074] The pretreated copper powder is prepared by the following steps:
[0075] (1) adding 13 parts by weight of copper powder to 100 parts by weight of dilute hydrochloric acid solution, stirring and mixing at room temperature for 18 minutes, filtering and taking the filter residue, adding 90 parts by weight of acetone, stirring and mixing at 55° C. for 20 minutes, filtering and removing the filtrate, and finally vacuum drying at 65° C. until constant weight, to obtain component A;
[0076] (2) adding 0.2 parts by weight of deionized water, 0.9 parts by weight of tetraethyl orthosilicate and 1 part by weight of aqueous ammonia to 75 parts by weight of anhydrous ethanol, stirring and mixing at 35° C. for 50 minutes, keeping the temperature, then adding 0.05 parts by weight of calcium nitrate and 0.07 parts by weight of silver nitrate, stirring and mixing for 25 minutes, to obtain component B;
[0077] (3) 18 parts by weight of anhydrous ethanol and 3 parts by weight of component A are added to component B, and then the mixture is stirred at 63° C. for 7 hours, dried, and calcined to complete the preparation.
[0078] The mass fraction of the dilute hydrochloric acid solution in step (1) is 6%.
[0079] The mass fraction of the ammonia water in step (2) is 25%.
[0080] The drying in step (3) refers to vacuum drying at 85° C. for 2 h.
[0081] The calcination in step (3) refers to heating to 380°C at a heating rate of 9°C / min under a nitrogen atmosphere and then calcining for 1.5 hours.
[0082] The inorganic binder is prepared by the following steps:
[0083] Silicon dioxide, boron trioxide, barium oxide, aluminum oxide, titanium oxide and lanthanum oxide are mixed in a mass ratio of 28:17:10:18:3.5:2, and then heated to 1550°C at a heating rate of 13°C / min and kept at a constant temperature for 25 minutes, quenched in water, and then vacuum dried at 35°C until constant weight, and ground to complete the preparation.
[0084] The grinding refers to grinding to a particle size of 1.7 μm.
[0085] The organic carrier is prepared by the following steps:
[0086] Add 2 parts by weight of thickener to 28 parts by weight of solvent, then stir at 93°C until completely dissolved, cool naturally to room temperature, then add 1 part by weight of surfactant and 1.7 parts by weight of dispersant, continue stirring for 9 hours, and finally let stand naturally for 23 hours to complete the preparation.
[0087] The solvent is terpineol.
[0088] The thickener is ethyl cellulose.
[0089] The surfactant is polyethylene glycol 400.
[0090] The dispersants are dibutyl phthalate and castor oil; the mass ratio of the dibutyl phthalate to the castor oil is 2:1.3.
[0091] A method for preparing an inner electrode copper paste for low temperature co-fired ceramics, the preparation method comprising the following steps:
[0092] The pretreated copper powder, the inorganic binder and the organic carrier are stirred and mixed at a stirring speed of 400 rpm at room temperature for 8 minutes to complete the preparation.
[0093] Comparative Example 1
[0094] On the basis of Example 3, calcium nitrate was replaced by an equal weight of silver nitrate, and the rest remained unchanged.
[0095] Comparative Example 2
[0096] Based on Example 3, silver nitrate was replaced by calcium nitrate of equal weight, and the rest remained unchanged.
[0097] Comparative Example 3
[0098] Based on Example 3, silver nitrate and calcium nitrate were replaced with anhydrous ethanol of equal weight, and the rest remained unchanged.
[0099] Comparative Example 4
[0100] Based on Example 3, step (2) and step (3) are not performed, and the rest remain unchanged.
[0101] Comparative Example 5
[0102] On the basis of Example 3, titanium oxide was not added during the preparation of the inorganic binder, and the rest remained unchanged.
[0103] Comparative Example 6
[0104] On the basis of Example 3, lanthanum oxide was not added during the preparation of the inorganic binder, and the rest remained unchanged.
[0105] Test Example 1
[0106] Conductivity test:
[0107] The inner electrode copper pastes prepared in Example 3 and Comparative Examples 1-6 were respectively printed on LTCC substrates (purchased from the 43rd Institute of China Electronics Technology Group Corporation) by screen printing to form copper films with a size of 10 mm*10 mm, and then dried at 90°C for 45 min, then heated to 400°C at a heating rate of 10°C / min in an air atmosphere and kept warm for 1 h, finally heated to 900°C at a heating rate of 10°C / min in a nitrogen atmosphere and kept warm for 1 h, and naturally cooled to room temperature to obtain sintered copper films with a thickness of 8 μm. The square resistance of the sintered copper films was tested using a four-probe square resistance meter, and one decimal place was rounded off.
[0108] Table 1. Conductivity test results
[0109] Square resistance / mΩ / □ Example 3 3.1 Comparative Example 1 3.6 Comparative Example 2 3.7 Comparative Example 3 4.0 Comparative Example 4 4.4 Comparative Example 5 3.6 Comparative Example 6 3.9
[0110] From the comparison of Test Example 1, Example 3 and Comparative Examples 1-6, it can be seen that the inner electrode copper paste prepared by the present invention is very suitable for application in low-temperature co-fired ceramics, which effectively reduces the oxidation of copper powder, improves the co-firing matching with the substrate, and enhances the conductive performance.
[0111] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A copper paste for inner electrodes of low temperature co-fired ceramics, characterized in that: The inner electrode copper paste is prepared from pretreated copper powder, an inorganic binder and an organic carrier; the mass ratio of the pretreated copper powder, the inorganic binder and the organic carrier is 70-80:5-7:
20.
2. The inner electrode copper paste for low temperature co-fired ceramics according to claim 1, characterized in that: The pretreated copper powder is prepared by the following steps: (1) adding 10-15 parts by weight of copper powder to 100 parts by weight of dilute hydrochloric acid solution, stirring and mixing at room temperature for 15-20 minutes, filtering and taking the filter residue, adding 80-100 parts by weight of acetone, stirring and mixing at 50-60° C. for 15-30 minutes, filtering and removing the filtrate, and finally vacuum drying at 60-70° C. until constant weight, to obtain component A; (2) adding 0.1-0.3 parts by weight of deionized water, 0.8-1 parts by weight of tetraethyl orthosilicate and 1 part by weight of aqueous ammonia to 70-80 parts by weight of anhydrous ethanol, stirring and mixing at 30-40° C. for 45-60 minutes, keeping the temperature, then adding 0.05 parts by weight of calcium nitrate and 0.05-0.08 parts by weight of silver nitrate, stirring and mixing for 20-30 minutes, to obtain component B; (3) Add 15-20 parts by weight of anhydrous ethanol and 3 parts by weight of component A to component B, then stir and mix at 60-65° C. for 6-8 hours, dry, and calcine to complete the preparation.
3. The inner electrode copper paste for low temperature co-fired ceramics according to claim 2, characterized in that: The mass fraction of the dilute hydrochloric acid solution in step (1) is 5-7%.
4. The inner electrode copper paste for low temperature co-fired ceramics according to claim 2, characterized in that: The mass fraction of the ammonia water in step (2) is 25%.
5. The inner electrode copper paste for low temperature co-fired ceramics according to claim 2, characterized in that: The drying in step (3) refers to vacuum drying at 80-90° C. for 2 h.
6. The inner electrode copper paste for low temperature co-fired ceramics according to claim 2, characterized in that: The calcination in step (3) refers to heating to 380°C at a heating rate of 8-10°C / min under a nitrogen atmosphere and then calcining for 1-2h.
7. The inner electrode copper paste for low temperature co-fired ceramics according to claim 1, characterized in that: The inorganic binder is prepared by the following steps: Silicon dioxide, boron trioxide, barium oxide, aluminum oxide, titanium oxide and lanthanum oxide are mixed in a mass ratio of 25-30:15-20:10:15-20:3-4:2, and then heated to 1500-1600°C at a heating rate of 10-15°C / min, kept at a constant temperature for 20-30 minutes, quenched in water, and then vacuum dried at 30-40°C until constant weight, ground, and the preparation is completed.
8. The inner electrode copper paste for low temperature co-fired ceramics according to claim 7, characterized in that: The grinding refers to grinding to a particle size of 1.5-1.8 μm.
9. The inner electrode copper paste for low temperature co-fired ceramics according to claim 1, characterized in that: The organic carrier is prepared by the following steps: Add 2 parts by weight of thickener to 25-30 parts by weight of solvent, then stir at 90-95°C until completely dissolved, cool naturally to room temperature, then add 1 part by weight of surfactant and 1.5-2 parts by weight of dispersant, continue stirring for 8-10 hours, and finally let stand naturally for 20-24 hours to complete the preparation.
10. A method for preparing an inner electrode copper paste for low temperature co-fired ceramics according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: The pretreated copper powder, the inorganic binder and the organic carrier are stirred and mixed at a stirring speed of 300-500 rpm at room temperature for 5-10 minutes to complete the preparation.
Citation Information
Patent Citations
Method for preparing copper electronic paste with excellent oxidation resistance
CN102938269A
Sr / Mg / Zn / Cu-doped silica-based sol-gel bioactive glass powder, and preparation method and application thereof
CN111908798A
Copper end electrode slurry and preparation method and application thereof
CN116844755A
Air sintering type copper paste and preparation method thereof
CN116936185A
High-speed low-loss hydrocarbon copper-clad plate and preparation method thereof
CN117774482A
